Mapping Research on Carbon Emissions in Sustainable Development Goals: A Bibliometric Analysis in Scopus Database - Haliza, Elza Fatika Nur; Bang, Aldous Billezra; Gunawan, Hendra; Paselle, Enos (Dinasti Publisher, 2025)
The intensifying global climate change has made carbon emissions a strategic issue in the sustainable development agenda. Carbon emissions, which mostly come from fossil fuel combustion, urbanization, and industrial activities, are a major contributor to global warming. In the context of the Sustainable Development Goals (SDGs), particularly SDG 13 on climate action, controlling carbon emissions is crucial. This study aims to map research trends on carbon emissions in relation to the SDGs through a bibliometric approach. Data were collected from the Scopus database for the 2014–2024 period using the keywords ‘carbon emissions’ and ‘sustainable development goals,’ then analyzed using VOSviewer software. The results show a significant increase in the number of publications each year, with a sharp spike from 2019 to 2024. Bibliometric visualization shows that themes such as